Comparison of the Effectiveness of Written Emotional Expression and Rational Emotive Behavior Therapy on the Health of Infertile Women - Gity, Sogol; Lotfi Kashani, Farah; Vaziri, Shahram; Namvar, Hooman (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The present study aimed to compare the effectiveness of the written emotional expression strategy and rational emotive behavior therapy (REBT) on the health of infertile women. Methods and Materials: The research method is quasi-experimental, and data collection was conducted using a pre-test, post-test, and follow-up design (three groups), with two experimental groups and one control group. The statistical population of this study consisted of all infertile women living in Tehran in 2023, who had visited infertility centers due to fertility problems and had been classified as infertile by obstetricians and gynecologists. From this population, 45 women were selected using a convenience sampling method and were randomly assigned to two experimental groups (15 participants in each group) and one control group (15 participants). The experimental group undergoing the written emotional expression strategy received eight sessions of 15 to 30 minutes each, while the experimental group undergoing rational emotive behavior therapy received 12 sessions of 60 minutes each. The control group remained on the waiting list. The tools used in the present study included the General Health Questionnaire (GHQ; Goldberg, 1972). Data analysis was performed using SPSS version 24, through both descriptive and inferential statistics (repeated measures ANOVA). Findings: The results indicated that both interventions (the written emotional expression strategy and rational emotive behavior therapy, in comparison to the control group) had an impact on the components of somatic symptoms, social dysfunction, depression, and anxiety/insomnia. Further, the amount of change in the written emotional expression group regarding the components of anxiety, insomnia, and depression was greater than in the rational emotive behavior therapy group. Conclusion: Therefore, considering the effectiveness of the interventions, it can be concluded that both educational interventions, by employing their specific techniques, improved the health of infertile women.